Impact of Energy Consumption on Industrial Growth in Nigerian Economy - Abdulkadir, Kassim Fatima; Isik, Abdurrahman (Journal of Advanced Research in Humanities and Social Sciences; Vol 7 No 3 (2020): Journal of Advanced Research in Humanities and Social Science, 2021)
This research investigates the impact of energy consumption on industrial growth. Manufacturing value added as proxy for industrial growth is used as dependent variable while the independent variables are; energy consumption, labor, and capital. The sample size covers a period of 29 years starting from 1990-2018. The OLS method of egression was used to estimate the equation in the period under review. Unit root test, Co-integration test and Granger causality were carried out to test for stationarity, long run relationship, and causal relationship, respectively. Result shows that there is a positive and significant relationship between energy consumption and manufacturing value added in the period under review. The unit root test shows that all variables are integrated of order one except for the variable capital, which is stationary at level. The Co-integration test indicates that there exists the presence of long-run relationships. The granger causality indicates the neutrality hypothesis in energy-industrial growth nexus in Nigeria. Generally, this paper stresses the dangers poor capacity of power generation from energy sources leading to inadequate electricity supply in the functioning of industries and businesses, which further worsens overall growth in the Nigerian economy. How to cite this article:  Abdulkadir KF, Isik A. Impact of Energy Consumption on Industrial Growth in Nigerian Economy. J Adv Res Humani Social Sci 2020; 7(3): 25-41.